1982
DOI: 10.1007/bf00432244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the novel compound aniracetam (Ro 13-5057) upon impaired learning and memory in rodents

Abstract: The effect of aniracetam (Ro 13-5057, 1-anisoyl-2-pyrrolidinone) was studied on various forms of experimentally impaired cognitive functions (learning and memory) in rodents and produced the following effects: (1) almost complete prevention of the incapacity to learn a discrete escape response in rats exposed to sublethal hypercapnia immediately before the acquisition session; (2) partial (rats) or complete (mice) prevention of the scopolamine-induced short-term amnesia for a passive avoidance task; (3) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
68
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(73 citation statements)
references
References 40 publications
3
68
2
Order By: Relevance
“…According to Olpe et al (1986) 1 mm oxiracetam is ineffective on the evoked responses in CAI. Since other in vitro studies with similar compounds (Satoh et al, 1986; and behavioural work (Cumin et al, 1982) showed a bell-shaped dose-effect relation, our findings may indicate the need to avoid unduly large concentrations of nootropics as their actions tend to dissipate following high doses.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…According to Olpe et al (1986) 1 mm oxiracetam is ineffective on the evoked responses in CAI. Since other in vitro studies with similar compounds (Satoh et al, 1986; and behavioural work (Cumin et al, 1982) showed a bell-shaped dose-effect relation, our findings may indicate the need to avoid unduly large concentrations of nootropics as their actions tend to dissipate following high doses.…”
Section: Discussionmentioning
confidence: 60%
“…In spite of the fact that differences in the action of piracetam and related nootropic drugs in many behavioural tests are seemingly related only to the doses used (Cumin et al, 1982;Schindler et al, 1984), the few data available for the electrophysiological effects of these drugs on the hippocampus suggest a different site and/or mechanism of action for each compound. Piracetam, for instance, has been found to increase reversibly the amplitude of the population spike, without any effect on the dentritic field e.p.s.p.…”
mentioning
confidence: 99%
“…Although some differences exist for training to test (retention test) intervals among the three PAR-failure models except for scopolamine PAR-failure in rats, these pro cedures may be considered to cause re trograde amnesia by impairing the memory consolidation process (8) For comparison, Ca-hopantenate which has been claimed to be effective for senile mental disorders (9), cholinomimetic agents (physostigmine and choline chloride) and nootropic agents (piracetam and aniracetam), which have also been reported to have beneficial effects on memory or cerebral impairment disorders (10-13), were also examined. In the ECS-PAR failure test, the retention test was performed at either 3 or 24 hr after the training.…”
Section: Discussionmentioning
confidence: 99%
“…This modification is induced via the aniracetam ability to bind to a putative allosteric site located in the extracellular loop between the TM3 and TM4 regions ofvarious molecular forms of AMPA receptors (18,19). It has been reported that aniracetam administered to rodents (20) and monkeys (16) antagonizes the cognition deficit induced by scopolamine, an acetylcholine muscarinic antagonist. Since aniracetam neither binds to nicotinic or muscarinic receptors nor inhibits acetylcholinesterases or high-affinity choline uptake, it has been considered an indirect cholinomimetic (21).…”
mentioning
confidence: 99%
“…However, in light of aniracetam's action on AMPA receptors, its reduction of scopolamine-induced amnesia could be attributed to the strengthening of the excitatory synaptic function linked to regulation of the cholinergic neurons that innervate neocortical and limbic structures (10). Although aniracetam and its congeners did not achieve a strong clinical endorsement because their action is weak and short lasting (22), these pyrrolidinone derivatives might nevertheless be viewed as prototypes of cognition enhancers that allosterically facilitate glutamatergic transmission without producing excitotoxicity or other adverse effects (5,23 (19,20,24), thereby allosterically facilitating AMPA receptor activity by inhibiting desensitization of glutamate-mediated synaptic transmission in hippocampus; the potency of IDRA 21 was found to be severalfold higher than that of aniracetam (24). Among various 1,2,4-benzothiadiazine derivatives that allosterically modulate AMPA cationic current in primary hippocampal neuronal cultures or in hippocampal slices (24,25), IDRA 21 given orally is the only known compound enhancing cognition in normal rats and potently antagonizing the cognition deficit elicited by the AMPA receptor antagonist 2,3-dihydro-6-nitro-7-sulfamoylbenzo(f)quinoxaline (NBQX) (10).…”
mentioning
confidence: 99%